DETECTION METHOD FOR CUTTER WEAR OF TBM BASED ON MAGNETOSTATIC EFFECT - HAN JiaLin (Jixie qiangdu)
The cutter wear of TBM significantly reduce the tunneling ability. For overcoming the defects of current testing method, the detection based on magnetostatic effect is proposed in this work. The proposed method greatly loosens the limitation of the protective shell material and has the advantage of high linearity. At first, the principle of detection method is presented, and the feasibility is investigated by finite element method. Secondly, the experimental equipment and signal processing circuit were built. The test results verify the linear variation feature between static magnetic force and wear loss. The gradient of static magnetic force is always about-592 mN/mm, which is much higher than the 25 mN accuracy of pressure sensor, so high accuracy was ensured.